Eicosanoids and other oxylipins in liver injury, inflammation and liver cancer development - Alba, Mario M.; Ebright, Brandon; Hua, Brittney; Slarve, Ielyzaveta; Zhou, Yiren; Jia, Yunyi; Louie, Stan G.; Stiles, Bangyan L. (Frontiers in Physiology, 2023)
Liver cancer is a malignancy developed with underlying liver disease that encompasses liver injury and metabolic disorders. The progression of these underlying liver disease to cancer is accompanied by chronic inflammatory conditions where liver macrophages play important roles in orchestrating the inflammatory response. During this process, bioactive lipids produced by hepatocytes and macrophages mediates the inflammatory responses by acting as both pro-inflammatory factors as well as playing roles in the resolution of inflammation conditions. Here, we reviewed the literatures discussing the roles of the bioactive lipids in acute and chronic hepatic inflammation and the progression to cancer.